PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PERSONIL POLTABEL YOGYAKARTA - Tony Wijaya (Media Riset Bisnis & Manajemen, 2007)
This research aims to know influence of Organizational Citizenship Behavior of compliance, participation and loyalty by simultant and parsial to personnel of Poltabes Yogyakarta is performance. The analyzed used in this research is multiple regression analysis.  Responder in this research amount to 70 personnel.  Pursuant to the result of research indicates that the variable of Organizational Citizenship Behavior have influence to performance of Poltabes Yogyakarta personnel.  Level of change of Yogyakarta personnel performance explained by compliance, participation and loyalty variables equal to 47% while other variables which explain variation of change of performance level of Poltabes Yogyakarta personnel is equal to 53%.  The most dominant factor that affects ont the Poltabes Yogyakarta personnel performance is participation.